Creative Elderly Productive Elderly Flower Arranging activities with the Elderly in Manukan, Tandes District, Surabaya City - Hariyana, Nanik; Takarini, Nurjanti; Mandasari, Virginia (Nusantara Science and Technology Proceedings, 2023)
Healthy and Independent Elderly Health. Viewed from the health aspect, the elderly group will experience a decline in their health status both naturally and as a result of disease. Therefore, as the number of elderly people increases, it is necessary from the start to prepare and plan various health programs aimed at the elderly. This activity aims to increase public knowledge in Manukan Kulon Village, Tandes District, Surabaya City about how to maintain the health of the elderly. Health education activities were carried out using the lecture method using PPT slides and leaflets, located in Manukan Kulon Village, Tandes District, Surabaya City. This activity, which was attended by 32 elderly people, ran smoothly and interactively. Health education activities ran smoothly and the community looked enthusiastic. The implementation of health education activities has gone smoothly according to the plans made, and the targets appear enthusiastic in participating in these activities.